siRNA-mediated stathmin1 silencing inhibits proliferation of prostate carcinoma cell line - Aksoy, Asude; Gokturk, Selcen; Etem Onalan, Ebru; Tektemur, Ahmet; Artas, Golchan; Varoglu, Asuman; Koc, Mustafa (Tubitak Scientific & Technological Research Council Turkey, 2022)
Stathmin1 (STMN1) has been proposed as a possible prognostic marker and a potential therapeutic target for some cancers. We aimed to analyze the changes in autophagy, invasion, apoptosis-related genes in prostate cancer (PCa) cell line (PC-3), after small interfering RNA (siRNA)-mediated STMN1 silencing, and also the relationships of STMN1 expression, clinicopathological parameters, and survival (OS) in PCa cases. The STMN1 expressions were analyzed, immunohistochemically, in formalin-fixed paraffin-embedded 75 PCa and 15 benign prostatic hypertrophy (BPH) tissues. The correlation between the levels of expression STMN1, clinicopathological features, and OS was determined in PCa cases. The siRNA-mediated STMN1 incubated PC-3 cells were transfected and compared to negative control siRNAs. We determined mRNA levels in autophagy, invasion, and apoptosis genes with the combination of reverse transcription-polymerase chain reaction (RT-PCR) and western blotting in PC3 cell lines after STMN1 silencing. It was determined that STMN1 was overexpressed significantly in PCa cases, immunohistochemically. The overexpression of STMN1 was significantly correlated with the high-grade Gleason score, and it was associated with a worse prognosis of PCa cases according to the Kaplan???Meier survival analysis (p < 0.05). Significant silencing in STMN1 was determined (87.5%) after siRNA applications. Especially, invasion genes such as claudin 7, fibroblast growth factor 8, hypoxia-inducible factor 1 subunit alpha, hepatocyte growth factor, matrix metallopeptidase 2, 7 genes, markedly, decreased by siRNA-mediated STMN1silencing. STMN1 silencing was determined to significantly increase caspase 3 protein expression by using western blot analysis (p < 0.001). Although STMN1 silencing did not have a significant effect on the induction of apoptosis and autophagy-related genes in PCa cells, it was shown to affect apoptotic mechanisms through the caps3 protein. siRNA-mediated STMN1 silencing decreases proliferation in the PCa cell line. It is thought that STMN1 can serve as a potential therapeutic target in the advanced stage-PCa, especially.
Keywords: Prostate cancer; Stathmin1; siRNA silencing; autophagy; invasion; apoptosis